Removal of Heavy Metals from Tie and Dye (Adire) Wastewater Using Low-Cost Adsorbents - Adekunle, Adebola Adebayo (Array, 2021)
Rapid industrialization has succeeded in constantly releasing hazardous heavy metals into the environment; however the need to minimize this risk has become a global concern. This study is to investigate the effectiveness of rice husk, sawdust and sugarcane bagasse as low cost adsorbents in heavy metals removal and to reduce the environmental pollution caused by these heavy metals. Columns of four different adsorbents (rice husk, sawdust, sugarcane bagasse and the mixture of the three) were set up and the Adire wastewater was passed through them. The adsorbents, the effluents and the filtrates were taken for physico-chemical and heavy metals analyses. The results shows that sugarcane bagasse adsorbent is the most effective in the physical and chemical treatment of the wastewater used, while the sawdust adsorbent is most effective in the removal of Copper, Chromium, Nickel and Iron.